Compressive strength and microstructure of 0-3 lead zirconate titanate ceramic-portland cement composites - Arnon Chaipanich (2018)
Lead zirconate titanate (PZT)-Portland cement (PC) composites have been reported to have good potential for use in smart structures. In this work, PZT-PC composites containing 40%, 50% and 60% of PZT by volume were produced and their mechanical and hydration properties were investigated. Compressive strengths of those typically used in normal concrete were found for all PZT-PC composites, with measured values of 41.5-45.0 MPa. Hydration products of Portland cement detected by thermal analysis were calcium silicate hydrates (the main cement hydration product), calcium hydroxide and ettringite. Furthermore, calcium silicate hydrates and ettringite can also be observed surrounding the PZT grains in the SEM micrograph. © 2013 Copyright Taylor and Francis Group, LLC.